2008
DOI: 10.1016/j.biocon.2008.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Coastal urbanization and the integrity of estuarine waterbird communities: Threshold responses and the importance of scale

Abstract: Biological indicator ChangepointLand cover Watershed A B S T R A C T Estuarine ecosystems are becoming increasingly altered by the concentration of human populations near the coastline, however a robust indicator of this change is lacking. We developed an index of waterbird community integrity (IWCI) and tested its sensitivity to anthropogenic activities within 28 watersheds and associated subestuaries of Chesapeake Bay, USA. The IWCI was used as a tool to gain insight into how human land use affects estuarine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…For example, the USGS identified urbanization as the driver for the 4% reduction in forested cover from 1973-2000 across the eastern U.S. (Drummond and Loveland 2010). Deluca et al (2008) found that development (e.g., urbanization and agriculture) near the estuarine coastlines of the Chesapeake Bay region is the main stressor affecting estuarine water bird community integrity, and that estuarine ecosystem integrity can be impaired even with extremely low levels of coastal urbanization. Urbanized watersheds in coastal southern California reduced native amphibian biodiversity and increased numbers of non-native crawfish (Riley et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the USGS identified urbanization as the driver for the 4% reduction in forested cover from 1973-2000 across the eastern U.S. (Drummond and Loveland 2010). Deluca et al (2008) found that development (e.g., urbanization and agriculture) near the estuarine coastlines of the Chesapeake Bay region is the main stressor affecting estuarine water bird community integrity, and that estuarine ecosystem integrity can be impaired even with extremely low levels of coastal urbanization. Urbanized watersheds in coastal southern California reduced native amphibian biodiversity and increased numbers of non-native crawfish (Riley et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, most estuarine marsh birds, who occupy higher trophic positions, may be vulnerable to these disturbances via bottom-up controls (DeLuca et al 2008;Cardoni et al 2011). Because natural and anthropogenic activities structuring marsh bird communities can span several connected regions (e.g., aquatic, semiterrestrial marsh, and terrestrial upland; DeLuca et al 2008) conservation measures aimed at achieving resilience of these communities will require protection of and connectivity between multiple adjoining habitats (Pringle 2001). …”
Section: Climate Change-associated Ecological Drivers: Impacts On Marmentioning
confidence: 99%
“…Predicting the response of estuarine ecosystems to changing environmental conditions is therefore challenging, as it necessitates understanding interactions among several trophic levels and multiple nutrient sources (marine, freshwater, and terrestrial) (Day et al 1993;Moody and Aronson 2007). Because birds are relatively well studied, they have been used to measure ecological conditions and evaluate the impacts of environmental change within tidal estuaries (Shriver et al 2004;DeLuca et al 2008). …”
Section: Introductionmentioning
confidence: 98%
“…An often cited rationale for the use of birds as ecosystem indicators is that most species occupy a relatively high trophic position; environmental conditions that affect basal productivity and physiochemical processes can affect marsh bird distributions from the "bottom up" (Novak et al 2005;DeLuca et al 2008). However, for some of these species, information on diet composition remains largely ancillary (based on gut content analysis and cast pellets), a situation particularly true for the clapper rail (Rallus longirostris).…”
Section: Introductionmentioning
confidence: 99%